Kiezen voor Kunst. - Paleis voor Schone Kunsten Brussel; Ampe, Dominique; Bex, Florent; Boucquet, Lieven; Broucke, Koen; Calle, Harald; Clement, Jan; De Greef, Hendrik; Desmet, Bernadette; Geysen, Jo; Helsen, Michel; Hoydonckx, Robert; et al. (Brussel : CSC Vormingswerk, 1995)
Ampe, Dominique ; Boucquet, Lieven ; Broucke, Koen ; Calle, Harald ; Clement, Jan ; De Greef, Hendrik ; Desmet, Bernadette ; Geysen, Jo ; Helsen, Michel ; Hoydonckx, Robert ; Hufkens, Marc ; Jacobs, Edwina ; Jacobs, Frie J. ; Jonckiere, Rogette ; Joostens, Kristien ; Keuten, Mario ; Lauwers, Karel ; Mecibah, Idir ; Mertens, Luc ; Meskens, Jeanne ; More Matter ; Mijngheer, Alain ; Muës, Jan ; Rasquinet, Josiane ; Sameyn, Damienne ; Schietecat, Crispian ; Seghers, Wilfried ; Suys, Marie Rose ; Trivier, Christian ; Tuyaerts, Peter ; Vanden Abbeele, Claire ; Van den Berghe, Ghis ; Vandepitte, Greet ; de Vijver, Wim Van ; de Wiele, Edwin Van ; Van Huffel, Dominique ; Vanmechelen, Koen ; Van Mierlo, Wim ; Verbeeren, Peter ; Verboven, Johan ; Verbruggen, Marc ; Vermeir, Jan ; Vermeire, Lut ; Verpuylt, Jean ; Vranken, Dominique
adres per kunstenaar
Nederlands
Kiezen voor kunst, Paleis voor Schone Kunsten Brussel, 17.11.1995 - 17.12.1995
boek